Statistics community portal [electronic resource] - California State University System; MERLOT (Multimedia Educational Resource for Learning and Online Teaching).; MERCED-I (Mindanao Educational Resources for Curricular Enhancement and Development-Initiatives) on OER (Open Educational Resources). (Long Beach, CA MERLOT, 1997)
Quoted from the homepage: "This site presents workbook-style, project-based material that emphasizes real world applications and conceptual understanding. This material is designed to give students a sense of the importance and allure of statistics early in their college career. By incorporating many of the successful reforms of the introductory statistics course into a wide range of more advanced topics we hope that students in any discipline can realize the intellectual content and broad applicability of statistics."
mixed.
online.
Keywords: Electronic information resources; Internet research; Internet in higher education; Open learning; Education, Higher; Electronic books; Bayesian analysis (Statistics) -- Open educational resource -- Electronic information resources; Brownian motion (Statistics) -- Open educational resource -- Electronic information resources; Data analysis (Statistics) -- Open educational resource -- Electronic information resources; Linear regression -- Open educational resource -- Electronic information resources; Markov chains (Statistics) -- Open educational resource -- Electronic information resources; Nonlinear regression -- Open educational resource -- Electronic information resources; Probability (Statistics) -- Open educational resource -- Electronic information resources; Queueing theory (Statistics) -- Open educational resource -- Electronic information resources; Statistcs -- Open educational resource -- Electronic information resources